Climate Change Implications for Indonesian Agriculture: A Systematic Literature Review - Trista Meilanie; Hamdi Akhsan; Kistiono (Mataram University, 2026)
Climate change is becoming an increasing threat to the food security of Indonesia, as it affects agricultural systems, changes the rainfall, raises sea levels, and intensifies extreme weather events. Conducted in the PRISMA protocol, this Review synthesizes the empirical evidence provided by 32 peer-reviewed articles, screened out of a preliminary set of 320 articles, published in 2020-25 in Google Scholar, Sinta, and ScienceDirect and in DOAJ. It is demonstrated that even a 1-2degC rise in temperature can lead to a 25 percent drop in national output of rice, salt intrusion along the coastlines can lower it by approximately 30 percent. Even though farmers have been engaging in different local adaptation responses such as reworking the planting calendars, they are usually stifled by lack of access to climate information, financial support, and technology. Among the mitigation alternatives, the Alternate Wetting and Drying (AWD) technique, 4R nutrient management, and peatland rehabilitation can be singled out as one of the most promising solutions to this issue as they allow mitigating greenhouse gas emissions and enhancing the agroecosystem resilience at the same time. This review suggests the incorporation of holistic adaptation and mitigation policies in national policies, institutional capacity building, and faster breeding and spreading of stress-resistant Plant varieties that can endure climatic change.